Redução de crômio hexavalente por substâncias húmicas aquáticas imobilizadas em aminopropil sílica - Romão, Luciane Pimenta Cruz (2002)
This paper describes the reduction of Cr(VI) to Cr(III) using a new support prepared by activation of aminopropyl silica with aquatic humic substances (ATPS-SiO2 -AHS). It were collected water samples from Córrego Itapitangui, Iguape, São Paulo State, Brazil according to the procedure recommended by the International Humic Substances Society. After purification by dialysis, aquatic humic substances were immobilized on aminopropyl silica (ATPS-SiO2 ) at pH 7.0, under mechanical stirring for 48 hours at room temperature. It were added 150 mg of ATPS-SiO2 -AHS in 150 mL of 9.5 mmol L-1 chromium solutions at pH 2.5, 4.5 and 6.0 under mechanical stirring at room temperature. Aliquots were collected in different times (0-72 hours) and Cr(VI) was determined by spectrophotometric method using the reaction with 1-5 diphenylcarbazide. The reduction per cent of Cr(VI) to Cr(III) by ATPS-SiO2 -AHS were 50; 4 and 0 % at pH 2.5, 4.5 and 6.0, respectively. At pH 2.5 using 300 mg of the support (ATPS-SiO2 -AHS) the chromium(VI) reduction increased to 70 %. This preliminary results shows strong influence of the pH and ATPSSiO2 -AHS concentration on Cr(VI) reduction process. The utilization of the support (ATPS-SiO2 - AHS) could be a future alternative for industrial effluents treatment and chromium speciation studies.